Iso Termiziy(R.A.) 'S Place In The Science Of Hadith. - Radjapova Marguba Zakirovna; Yunusova Buxajal Alimovna (Zien Journals, 2022)
The article discusses the origin of the word "Hadith" and its meaning in the term. The role and advantages of Isa Termizi's work "Sunani Termizi" in the Islamic world are described.
Keywords: hadith; sunnah; taqrir; sahih